Панцирные клещи (Acariformes, Oribatei) отделения «Каменные могилы» Украинского государственного степного заповедника АН УССР - Усова, З.В.; Ярошенко, Н.Н. (Вестник зоологии, 1971)
In 1969 the beetle mite fauna of virgin steppe was investigated in the territory of the «Kamennye mogily» division (the Donetsk region). The material was collected in four biotopes: true and stony steppes in granite outcrops in platforms and ridge fissures. 90 species of beetle mites are found belonging to 55 genera and 37 families: 55 of them — in true steppe, 54 — in stony steppe, 52 — in ridge fissures and platforms of rocks, 31 — in mosses and lichens in granite outcrops. The species Metabelba ericius К u n s t, 1957 is mentioned for the first time for the Ukrainian SSR, Zygoribatule, sp. n. is new for science. 16 species of beetle mites are intermediate hosts of cestoda (Anoplocephallidae) of domestic animals.